Indicators for identification of urban flooding vulnerability - Barroca, B.; Bernardara, P.; Mouchel, J.M.; Hubert, G. (Natural Hazards and Earth System Sciences, 2006)
In the last 5 years in France, we have observed that each new flood event exposes the weaknesses of the existing prevention system as well as the local weakness. Such events raise questions about the relevance and the effectiveness of the means of prevention. But these events also reveal resistance of the exposed territories, which shows that effective and adequate local strategies exist. There are various methods to evaluate the weakness, or vulnerability of an area, but since the last ten years the qualitative approach of vulnerability in flood risks became more important. Nevertheless, local authorities are often unable to evaluate the vulnerabilities of their territory. Local decision makers request tools for a better assessment of flooding vulnerability. Thus, many approaches of the weakness and the resistance of frequently flooded territories were developed on various scales. These approaches are often partial and contextual. There is a clear need for a support of the evaluation of vulnerability. However, there are obvious synergies between these different approaches, with regard to data retrieval and the establishment of adequate information systems taking into account the vulnerability of a specific territory. The paper develops a methodology aimed to organize into a software toot the choice of vulnerability indicators and the integration of the point of view of various stakeholders (economists, town planners, experts, political leaders, etc). This challenge is based on three simple statements: break down of the problems of vulnerability into homogeneous subsets and manage them; articulation of these subsets in a graphical interface allowing the presentation of interactions between the indicators of vulnerability and compare the opposed visions of vulnerability. The interface of the tool integrates various vulnerability indicators, which are organised in several categories, in order to allow a flexible and efficient vulnerability analysis.